“Insights into vessel perforations during thrombectomy - Schulze-Zachau, Victor (2024)
Funding Information: The author(s) declared the following potential conflicts of interest with respect to the research, authorship, and/or publication of this article: V. S.-Z. discloses speaker fees from Medtronic Inc. (money paid to institution).\u2009M.R.L. discloses unrestricted educational grants from Medtronic and Stryker; consulting for Medtronic, Stereotaxis, Metis Innovative and Aeaean Advisers; equity interest in Proprio, Fluid Biomed, Stroke Diagnostics, Hyperion Surgical, Apertur; editorial board of Journal of NeuroInterventional Surgery; data safety monitoring board of Arsenal Medical. M.-N.P. discloses unrestricted grants from Swiss National Science Foundation (SNF), Bangerter-Rhyner Stiftung, Stryker Neurovascular Inc., Phenox GmbH, Medtronic Inc., Rapid Medical Inc., and Penumbra Inc for the DISTAL trial, grant for SPINNERS trial from Siemens Healthineers AG (money paid to institution) and the following speaker fees: Stryker Neurovascular Inc., Medtronic Inc., Penumbra Inc., Acandis GmbH, Phenox GmbH, Rapid Medical Inc. and Siemens Healthineers AG (money paid to institution). Funding Information: The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: No project-specific funding was received for this study. V.S.-Z. is recipient of a research grant from Basel University, Basel, Switzerland. Publisher Copyright: © European Stroke Organisation 2024.